Workshop Kelas Riset Dan Publikasi Ilmiah Untuk Mahasiswa Jurusan Biologi Di Uin Walisongo Semarang - Wijayanti, Erna (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2023)
Research skills, writing scientific articles, and scientific publications are essential for students. The purpose of this service program is to provide education to the participants in research, article writing, and scientific journals. This service program used the Asset Based for Community Development (ABCD) method. This service has five stages: potential identification, asset mapping, program analysis, program implementation, and evaluation. The service results showed that the service participants have writing potential that can be developed. The program chosen is a workshop. After attending the workshop, the participants could conduct research in the field of Biology, write the research results in scientific articles and submit them to appropriate national journals. It is hoped that this service program will not only be carried out among students but can also be carried out with a broader range of participants such as teachers, students, or santri.